Multiple intra-hepatic and abdominal splenosis: an easy call if you know about it. (May 2018) - Vergara, Doriana; Ginolfi, Francesco; Moscati, Stefano; Giordano, Beniamino; Ferrara, Nicola; Panico, Camilla; Imbriaco, Massimo
Hepatic splenosis represents the heterotopic implantation of splenic tissue caused by the spillage of cells from the spleen usually after splenectomy or splenic trauma. This condition is usually an incidental finding during surgery and its real incidence is unknown. Splenic implants, which can be placed anywhere in the abdominal cavity, are usually multiple and may be confused with different benign and malignant conditions such as renal tumors, abdominal lymphomas, and endometriosis. We hereby report an unusual case of multiple abdominal splenosis, with a particular intra-hepatic location, that could be misinterpreted as an hepato-cellular carcinoma.